Sorting Motifs Involved in the Trafficking and Localization of the PIN1 Auxin Efflux Carrier. Issue 3 (12th May 2016) - Sancho-Andrés, Gloria; Soriano-Ortega, Esther; Gao, Caiji; Bernabé-Orts, Joan Miquel; Narasimhan, Madhumitha; Müller, Anna Ophelia; Tejos, Ricardo; Jiang, Liwen; Friml, Jiří; Aniento, Fernando; Marcote, María Jesús
Abstract : Phenylalanine 165 is important for PIN1 endocytosis and its trafficking through the secretory pathway. Abstract: In contrast with the wealth of recent reports about the function of μ-adaptins and clathrin adaptor protein (AP) complexes, there is very little information about the motifs that determine the sorting of membrane proteins within clathrin-coated vesicles in plants. Here, we investigated putative sorting signals in the large cytosolic loop of the Arabidopsis ( Arabidopsis thaliana ) PIN-FORMED1 (PIN1) auxin transporter, which are involved in binding μ-adaptins and thus in PIN1 trafficking and localization. We found that Phe-165 and Tyr-280, Tyr-328, and Tyr-394 are involved in the binding of different μ-adaptins in vitro. However, only Phe-165, which binds μA(μ2)- and μD(μ3)-adaptin, was found to be essential for PIN1 trafficking and localization in vivo. The PIN1:GFP-F165A mutant showed reduced endocytosis but also localized to intracellular structures containing several layers of membranes and endoplasmic reticulum (ER ) markers, suggesting that they correspond to ER or ER -derived membranes. While PIN1:GFP localized normally in a μA (μ2)-adaptin mutant, it accumulated in big intracellular structures containing LysoTracker in a μD (μ3)-adaptin mutant, consistent with previous results obtained with mutants of other subunits of the AP-3 complex. Our data suggest that Phe-165, through the binding of μA (μ2)- and μD (μ3)-adaptin, is important for PIN1 endocytosis and for PIN1 trafficking along the secretory pathway, respectively.